Pengendalian Persaingan Monopoli dalam Hukum Perdata: Upaya Perlindungan Konsumen dan Pengusaha Kecil - Stevanny Stevanny; Ni Luh Vita Widyasari Susrama Putri (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
Monopolistic competition is a profound issue in civil law and has the potential to threaten the business ecosystem and consumer rights. This journal aims to investigate efforts to control monopolistic competition through a civil law perspective, with an emphasis on the protection of consumers and small entrepreneurs. The study utilizes an analytical and comparative law approach to identify the applicable legal framework in various jurisdictions, focusing on recent cases involving monopolistic competition. The findings of this study show that civil law has a significant role to play in the control of monopolistic competition by protecting consumer rights and regulating business practices that may hinder competition. The research also highlights the challenges faced in applying civil law in monopolistic competition cases and striking the right balance between consumer protection, small entrepreneurs, and economic sustainability. Legislative and judicial efforts undertaken by various countries are also analyzed to assess the effectiveness of monopoly competition control in supporting a fair and competitive economy. The results of this study provide a deeper understanding of the role of civil law in the control of monopolistic competition and its implications for the protection of consumers and small businesses. The practical implication of this research is the importance of strict supervision of monopolistic practices, strong consumer protection policies, and cooperation between various related parties to maintain a healthy business ecosystem.